Special considerations for working with parents and caregivers - Sassu, K.A. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
Parents and caregivers of individuals with autism spectrum disorder (ASD) are faced with unique challenges and stressors from the early stages of their children’s development, through subsequent diagnosis, navigating the educational and therapeutic landscapes, and into adulthood. Whether their child requires Level 1, 2, or 3 supports according to their Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition diagnosis, parents will be faced with many different types of stressors. Given their experiences and knowledge of their children, they can offer valuable insights to educators and service providers that inform interventions and lead to optimal outcomes for individuals with ASD. This chapter explores the common challenges encountered by parents and caregivers and offers suggestions for ways that professional educators can best engage with them so as to establish optimal supports for individuals with autism. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.csp